Webster, Rooks County - Chesney, Billie (Kansas State University, The Chapman Center for Rural Studies, 2012)
Webster was a failed railroad town that, despite its unity and perseverance, was sacrificed to the creation of Webster Reservoir. This case study includes photographs, maps, and interviews from Mrs. Jean Lindsey, local historian, and Mrs. Patty Chesney.
Billie Chesney, “Webster, Rooks County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/105.
Keywords: Webster; Rooks County; Old Webster; Webster Dam; Woodston; Belmont